Children, youth and time - Schutter, Sabina; Harring, Dana (Sociological studies of children and youth, 2022)
The concept of time in childhood and youth is discussed in two contradictory ways; first romanticized, as a time of play, innocence, and exploration - of learning through trial and error, and second, as a time restricted by tight societal and generational structures, such as chains of care, institutional and family timetables. Children, Youth and Time reflects on the complex concept of time as perceived and experienced by children and young people in relevant societal and generational contexts. Including empirical and theoretical contributions from around the globe which shed light on time and temporality as it is negotiated by children and young people in distinction to adults, both within the family and in institutional contexts, the chapters in this collection delve into the impact of current global challenges upon children, young people, and families' time. How do critical global concerns such as climate change or the COVID-19 pandemic affect the temporal experience of children and youth? Providing fresh insight at a crucial moment of global disruption, the authors equip us with a stronger awareness of young people's perceptions of the world during periods of crisis. As a vital tool for safeguarding and implementing strategies to support children and young people in an everchanging world, this is a timely resource for researchers interested in the welfare of children and youth.